2013
DOI: 10.1002/chem.201301194
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Study of Fluorescence‐Based Detection of Nitroexplosives and Other Aromatics in the Vapor Phase by Microporous Metal–Organic Frameworks

Abstract: A systematic study is conducted on four microporous metal–organic framework compounds built on similar ligands but different structures, namely [Zn3(bpdc)3(bpy)]⋅4 DMF⋅H2O (1), [Zn3(bpdc)3(2,2′dmbpy)]⋅4 DMF⋅ H2O (2), [Zn2(bpdc)2(bpe)]⋅2 DMF (3), and [Zn(bpdc)(bpe)]⋅DMF (4) (bpdc=4,4′‐biphenyldicarboxylate; bpy=4,4′‐bipyridine; 2,2′dmbpy=2,2′‐dimethyl‐4,4′bipyridine; bpe=1,2‐bis(4‐pyridyl)ethane; DMF=N,N′‐dimethylformamide) to investigate their photoluminescence properties and sensing/detection behavior upon ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
97
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 206 publications
(99 citation statements)
references
References 71 publications
2
97
0
Order By: Relevance
“…The fluorescence quenching phenomenon should be mainly due to electron transfer from the framework to electron-deficient NB molecule. [58,59] The absorption band of TNP has a 20 considerable degree of overlap with the emission spectrum of JUC-135 in DMF (Fig. So we 60 further investigated the fluorescent property of JUC-135 to detect a series of nitroaromatic explosives, including 1, 3-DNB, 2, 4-DNT and TNP.…”
Section: Fluorescent Behavior and Sensing Propertiesmentioning
confidence: 99%
“…The fluorescence quenching phenomenon should be mainly due to electron transfer from the framework to electron-deficient NB molecule. [58,59] The absorption band of TNP has a 20 considerable degree of overlap with the emission spectrum of JUC-135 in DMF (Fig. So we 60 further investigated the fluorescent property of JUC-135 to detect a series of nitroaromatic explosives, including 1, 3-DNB, 2, 4-DNT and TNP.…”
Section: Fluorescent Behavior and Sensing Propertiesmentioning
confidence: 99%
“…MOFs with metal centers of europium, cadmium, zinc, lithium, iridium have been recently reported for the detection of nitro-aromatic explosives [22][23][24][25][26]. However, some of our tests on the nitro aromatic explosive sensing with MOFs revealed that, at times, it is difficult to obtain reproducible results in different sets of experiments.…”
Section: Introductionmentioning
confidence: 71%
“…In general, the electron transfer from the conduction band (CB) of the MOFs in the excited state to the low-lying lowest unoccupied molecular orbital (LUMO) of the analytes will result in a fluorescence quenching effect. [31,32] The fact that p-nitroaniline exhibits the strongest quenching effect may be attributed to the strongly electron-withdrawing NO 2 group. In contrast, if the excited electrons are transferred from a high-lying π* type LUMO orbital to the conduction band of MOF1, fluorescence enhancement will result.…”
Section: Detection Of Aromatic Aminesmentioning
confidence: 98%